PES composite ultrafiltration membrane based on MXene material modification and preparation method thereof

By introducing MXene and SnO2 into the PES ultrafiltration membrane, a composite membrane with excellent anti-pollution and separation performance was prepared, which solved the problem of existing PES ultrafiltration membranes being susceptible to contamination when dealing with contaminated water sources, achieving a longer service life and lower production costs.

CN119701669AActive Publication Date: 2025-03-28ZHONGKE LINGGU NEW MATERIALS LAB (SHENZHEN) CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411905335.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

Existing PES ultrafiltration membranes are susceptible to contamination when dealing with contaminated water sources, resulting in a decrease in membrane flux, a shortened service life and an increase in production costs. The membrane structure is difficult to regulate, and the preparation results are not repetitive.

Method used

By introducing two-dimensional structural transition metal carbon/nitride (MXene) materials and metal oxide (SnO2) into the polymer ultrafiltration membrane, the MXene/SnO2/PES composite membrane with excellent anti-pollution and separation properties were prepared by blend-phase conversion method.

Benefits of technology

It improves the anti-pollution and separation ability of the composite film, extends the service life of the film, reduces production costs, and improves the mechanical strength and stability of the film, maintaining high permeability and selectivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701669A_ABST
    Figure CN119701669A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer materials, and particularly relates to a PES composite ultrafiltration membrane based on MXene material modification and a preparation method of the PES composite ultrafiltration membrane, and the preparation method comprises the following steps: (1) weighing the following raw materials in percentage by mass: 16-20% of modified PES powder, 0.08-0.13% of SnO2, 0.01-0.03% of MXene, 0.8-1.5% of PVP and the balance of DMAc; (2) SnO2, MXene and PVP are dispersed in DMAc, then ultrasonic treatment is conducted for 1-3 h, and a mixture is obtained; (3) preparing pouring liquid; and (4) defoaming the pouring liquid, uniformly smearing the pouring liquid on a glass plate at room temperature, and then placing the glass plate in a deionized water coagulation bath to obtain the PES composite ultrafiltration membrane based on MXene material modification. The ultrafiltration membrane prepared by the invention has excellent protein pollution resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of organic polymer materials, and specifically relates to a PES composite ultrafiltration membrane modified based on a MXene material and a preparation method thereof. Background Art

[0002] Membrane separation technology refers to the technology of using water treatment membranes to screen molecular mixtures of different particle sizes. It does not involve phase change and has no secondary pollution, and has important practical significance in the recycling of water resources. Ultrafiltration (UF) is one of the most popular wastewater treatment technologies in membrane technology because it has potential advantages in separating large molecules, bacteria, heavy metals and dyes, and specific compounds. However, in the process of treating polluted water sources, the deposition of pollutants on the membrane will cause serious membrane fouling, which will affect the permeability and selectivity of the membrane, shorten the life of the membrane, and increase maintenance costs and design complexity. Therefore, how to prevent membrane fouling or slow down the membrane fouling process has always been the focus of scientific research and industrial application research.

[0003] Polyethersulfone (PES) membrane is a polymer membrane material with excellent comprehensive performance, which has been widely used in sewage treatment, seawater desalination, food processing and biomedicine. Although PES has good chemical stability, compared with a variety of membrane materials, its hydrophilicity is relatively low, and it has strong hydrophobicity and pore size non-uniformity. It is easy to adsorb hydrophobic substances such as colloids and proteins during the membrane making process, which can easily cause membrane pollution. Membrane pollution will bring about a series of problems such as decreased membrane flux, shortened service life, and increased production costs, which hinders the practical application of PES ultrafiltration membranes in sewage treatment and the further promotion and application of ultrafiltration technology.

[0004] Polyethersulfone (PES) polymers are widely used in the manufacture of ultrafiltration membranes due to their excellent acid and alkali resistance, physical and chemical resistance, film-forming properties and thermal stability. However, in the current PES ultrafiltration membrane preparation process, there are problems such as difficult to control the membrane structure and low repeatability of the preparation results. PES is also prone to adsorb hydrophobic substances such as colloids and proteins during the membrane preparation process due to its strong hydrophobicity and uneven pore size, which can easily lead to membrane contamination. However, membrane contamination will limit the service life, membrane flux and production cost of the PES ultrafiltration membrane, hindering the application and development of ultrafiltration technology.

[0005] Therefore, there is an urgent need for a PES composite ultrafiltration membrane modified based on MXene materials and a preparation method thereof. Summary of the invention

[0006] The purpose of the present invention is to provide a PES composite ultrafiltration membrane modified based on MXene material and a preparation method thereof.

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] The present invention provides a method for preparing a PES composite ultrafiltration membrane modified by a MXene material, comprising the following steps:

[0009] (1) Weigh the raw materials according to the following mass percentages: 16-20% modified PES powder, 0.08-0.13% SnO2, 0.01-0.03% MXene, 0.8-1.5% PVP and the balance DMAc;

[0010] (2) SnO2, MXene and PVP were dispersed in DMAc and then ultrasonically treated for 1-3 h to obtain a mixture;

[0011] (3) adding the modified PES powder to the mixture and stirring at 60-90° C. for 4-8 hours until the PES powder is completely dissolved to obtain a casting solution;

[0012] (4) Defoam the casting liquid and use a casting blade (200 μm) to evenly apply the casting liquid to a smooth glass plate at room temperature. Then slowly place the glass plate in a deionized water condensation bath. As the phase change is completed, the membrane automatically separates from the glass plate. Keep the membrane in deionized water for 12-24 hours to fully remove excess solvent, thereby obtaining a PES composite ultrafiltration membrane modified based on MXene materials.

[0013] Furthermore, SnO2 comprises tin oxide A, tin oxide B and tin oxide C in a mass ratio of 1: (1.2-1.5): (0.4-0.7); the average particle size of tin oxide A is 20-50nm, and the specific surface area is 75-98m 2 / g; the average particle size of tin oxide B is 150-200nm, and the specific surface area is 34-51m 2 / g; the average particle size of tin oxide B is 300-400nm, and the specific surface area is 9-16m 2 / g; all ordered from Beijing Juguang Yingnik Technology Co., Ltd.

[0014] The present invention introduces two-dimensional structure transition metal carbon / nitride (MXene) into a polymer ultrafiltration membrane mixed with tin oxide, and the two produce a synergistic effect, which not only improves the anti-pollution ability of the composite membrane, but also improves the separation ability of the composite membrane. The present invention can improve the flux and retention rate of the PES composite ultrafiltration membrane modified based on MXene material for BSA solution by adding tin oxide compounded in a specific ratio. Mainly, SnO2 particles of different particle sizes after compounding can form a more uniform and reasonable pore structure inside the membrane, thereby improving the retention rate. At the same time, the mechanical strength and stability of the membrane can be increased, making the membrane less likely to deform or break during the filtration process. This not only helps to maintain the physical integrity of the membrane, but also maintains stable performance under high-pressure operating conditions; the different particle sizes and surface areas of SnO2 will affect the hydrophilicity and charge characteristics of the membrane surface; appropriately adjusting these parameters can make the membrane surface more hydrophilic, reduce the adsorption of biological molecules such as proteins, and reduce the risk of membrane pollution, thereby maintaining a higher flux.

[0015] Furthermore, MXene is a Ti3C2Tx sheet with 1-5 layers and a radial size of 0.5-2 μm.

[0016] Furthermore, the viscosity average molecular weight of PVP is 3000-7000 and is purchased from Boai Xinkaiyuan Medical Technology Group Co., Ltd.

[0017] Further, the preparation method of the modified PES powder comprises the following steps:

[0018] (1) mixing hydroquinone, 2,5-dihydroxyterephthalic acid, 4,4'-dichlorodiphenyl sulfone, dimethyl sulfoxide, toluene and anhydrous potassium carbonate, heating to 150-155° C. under nitrogen protection and stirring, keeping the temperature for reaction for 4-6 hours, raising the temperature to 168-170° C. and continuing the reaction for 4-6 hours to obtain a polymer product; cooling and solidifying the polymer product, crushing it, washing it with boiling deionized water for 2-3 times, and then reflux acidifying it with hydrochloric acid having a concentration of 36-38wt% for 25-30 hours, filtering it with suction, washing it with deionized water, drying it, and crushing it to a particle size of less than 9 μm to obtain a carboxylated modified polyether sulfone powder;

[0019] (2) 3-isocyanatepropyltrimethoxysilane (CAS: 15396-00-6, purchased from Shanghai Ruichu Biotechnology Co., Ltd.) and carboxylated modified polyethersulfone powder were mixed and subjected to ultrasonic treatment for 20-30 min; toluene was then added, heated to 105-100° C. and stirred for reaction for 2-3 h, and toluene was recovered by vacuum distillation. The solid product was washed with ethanol for 2-3 times and freeze-dried to obtain silane-modified polyethersulfone powder;

[0020] (3) adding 0.03 parts by weight of silane-modified polyethersulfone powder to 30-35 parts by weight of ethanol and ultrasonicating for 20-30 minutes to prepare an alcohol solution; weighing 0.03 parts by weight of nano-TiO2 and adding it to 25-30 parts by weight of deionized water, and ultrasonicating for 20-30 minutes to prepare a TiO2 aqueous solution;

[0021] (4) Under stirring conditions, the TiO2 aqueous solution is added dropwise to the alcohol solution, heated to 60-65°C, stirred for reaction for 2-4 hours, centrifuged to remove the supernatant, washed with deionized water 3-4 times, and freeze-dried to obtain modified PES powder.

[0022] Further, the masses of hydroquinone, sodium 3-(4-(-2,6'-difluorophenylcarbonyl)phenyl)propanesulfonate, 4,4'-difluorodiphenyl sulfone, dimethyl sulfoxide, toluene and anhydrous potassium carbonate are (6-8):(13-15):(43-45):(290-300):120:(72-75).

[0023] Furthermore, the mass ratio of 3-isocyanatepropyltrimethoxysilane, carboxylation-modified polyethersulfone powder and toluene is (1-1.2):0.1:(60-70).

[0024] Furthermore, the mass ratio of the silane-modified polyethersulfone powder to the nano-TiO2 is 10:(1-3).

[0025] Furthermore, the nano-TiO2 includes nano-TiO2Ⅰ, nano-TiO2Ⅱ and nano-TiO2Ⅲ in a mass ratio of (1.3-1.5):1:(0.5-0.7); the average primary particle size of TiO2Ⅰ is 15nm, and the specific surface area is 30-100m 2 / g (Model DK405); the average primary particle size of nano-TiO2Ⅱ is 60nm, and the specific surface area is 20-60m 2 / g (DK405-2) and the average primary particle size of nano-TiO2Ⅲ is 200nm, and the specific surface area is 15m 2 / g(DK405-3). Purchased from Beijing Dekedao Gold Technology Co., Ltd.

[0026] The commercially available PES powder is highly hydrophobic, which is not conducive to the easy adsorption of hydrophobic substances such as colloids and proteins during the membrane making process, and it is very easy to cause membrane pollution. The present invention prepares modified PES powder, uses carboxyl groups and titanium oxide grafted on the PES powder, and is convenient for binding more water molecules through hydrogen bonding. Nano-scale TiO2 particles can provide more surface hydroxyl sites, which can form stronger interactions with water molecules, further improve the hydrophilicity of the material, and thus increase its anti-fouling performance. At the same time, it can also improve the long-term stability of the PES composite ultrafiltration membrane modified based on MXene materials.

[0027] The second aspect of the present invention provides a PES composite ultrafiltration membrane modified based on MXene materials obtained by the preparation method.

[0028] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0029] 1. To solve the above problems, photocatalytic materials can be combined with traditional polymer membranes. The photocatalytic materials can effectively degrade dye pollutants under light, which can effectively improve the active antifouling ability of PES-based ultrafiltration membranes, and is expected to provide valuable solutions for wastewater treatment applications. MXene is a class of two-dimensional inorganic compounds in materials science. These materials are composed of transition metal carbides, nitrides or carbonitrides with a thickness of several atomic layers. In this study, two-dimensional transition metal carbon / nitride (MXene) materials with photocatalytic properties and metal oxides were loaded into PES membranes through blending and phase conversion methods to prepare MXene / SnO2 / PES composite membranes with excellent anti-protein fouling properties.

[0030] 2. The present invention prepares PES membranes with different SnO2 / MXene contents by blending-phase conversion method. Among them, the unique surface function of MXene can provide a broad platform for SnO2 nanoparticles and a large number of active sites to load SnO2 nanoparticles, thereby generating a large number of photogenerated electrons, improving the photodegradation effect of pollutants, while maintaining high permeability. The resulting SnO2-MXene / PES membrane with antifouling and self-cleaning properties can be used in the field of sewage treatment.

[0031] 3. The present invention introduces a metal oxide (SnO2) with photocatalytic properties into a polymer ultrafiltration membrane (PES), and utilizes its photocatalytic properties to quickly degrade pollutants, thereby obtaining a method for preparing a novel ultrafiltration membrane with anti-pollution activity. In order to increase the loading capacity of the polymer membrane for the photocatalyst, the present invention introduces a two-dimensional structured transition metal carbon / nitride (MXene) into a polymer ultrafiltration membrane mixed with a metal oxide. The two produce a synergistic effect, which not only improves the anti-pollution ability of the composite membrane, but also improves the separation ability of the composite membrane.

[0032] 4. Polyethersulfone (PES) polymers have fewer active sites, and their loading capacity for nano-metal oxides is far from reaching the active antifouling performance. In order to increase the capacity of the polymer membrane, it is necessary to introduce more active sites to improve its catalytic performance. However, the increase in active sites leads to an increase in the loading of the polymer membrane on the catalytic material, which further promotes the agglomeration of the catalytic material and the formation of non-selective voids in the polymer membrane, seriously affecting the selectivity of the membrane. Therefore, the balance between the membrane separation function and the photodegradation ability is the key to building a high-performance ultrafiltration membrane. MXene, as an emerging two-dimensional (2D) structured transition metal carbon / nitride material, has excellent properties such as high specific surface area, hydrophilicity and high carrier mobility, and exhibits excellent dye separation efficiency in catalytic membrane-based water treatment. As a two-dimensional material with a high specific surface area, MXene has abundant active sites, which can greatly enhance the loading capacity of metal oxide materials. MXene nanosheets are used to achieve solute retention and create electron transfer channels for photocatalytic particles to reduce photogenerated electron-hole complexation and improve the membrane photocatalytic efficiency. In addition, MXene has made a good contribution to improving the hydrophilicity of polymer membranes and mitigating membrane fouling due to its rich surface functional groups (-OH, -F, -O) and high adsorption. Among wide bandgap semiconductors, SnO2 has unique advantages in long-term stability, rich micromorphology and excellent biocompatibility. In addition to the catalytic effect, the introduction of SnO2 can also improve the mechanical properties of polymer membranes. Therefore, the introduction of MXene and SnO2 in polymer membranes is an effective strategy to solve the problem of membrane fouling.

[0033] 5. The present invention can improve the flux and retention rate of BSA solution of the PES composite ultrafiltration membrane modified based on MXene materials by adding tin oxide compounded in a specific ratio.

[0034] 6. The present invention can improve the hydrophilicity of the PES composite ultrafiltration membrane modified by MXene materials by preparing modified PES powder, thereby increasing its anti-fouling performance. At the same time, it can also improve the long-term use stability of the PES composite ultrafiltration membrane modified by MXene materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 It is a contact angle comparison diagram of Example 1 and Comparative Example 2;

[0036] Figure 2 This is a schematic diagram of the PES flux and interception test results before and after modification in Example 1;

[0037] Figure 3 This is a schematic diagram of the self-cleaning performance test results of the PES membrane in Example 2;

[0038] Figure 4 Schematic diagram of the flux and interception test results of methylene blue before and after modification in Example 3. DETAILED DESCRIPTION

[0039] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] The mass percentages of the raw materials used in Examples 1-3 and Comparative Examples 1-3 are shown in Table 1:

[0041] Table 1 Preparation parameters of composite membranes with different MXene / SnO2 / PES ratios

[0042]

[0043] Example 1

[0044] This embodiment provides a method for preparing a PES composite ultrafiltration membrane modified by a MXene material, comprising the following steps:

[0045] (1) Weigh the corresponding raw materials according to Table 1;

[0046] (2) SnO2, MXene and PVP were dispersed in DMAc and then ultrasonically treated for 1-3 h to obtain a mixture;

[0047] (3) adding the modified PES powder to the mixture and stirring at 80° C. for 6 hours until the PES powder is completely dissolved to obtain a casting solution;

[0048] (4) Defoam the casting liquid and use a casting blade (200 μm) to evenly apply the casting liquid to a smooth glass plate at room temperature. Then slowly place the glass plate in a deionized water condensation bath. As the phase change is completed, the membrane automatically separates from the glass plate. Keep the membrane in deionized water for 20 hours to fully remove excess solvent, thereby obtaining a PES composite ultrafiltration membrane modified based on MXene materials.

[0049] SnO2 includes tin oxide A, tin oxide B and tin oxide C in a mass ratio of 1:1.3:0.5; the average particle size of tin oxide A is 20-50nm, and the specific surface area is 75-98m 2 / g; the average particle size of tin oxide B is 150-200nm, and the specific surface area is 34-51m 2 / g; the average particle size of tin oxide B is 300-400nm, and the specific surface area is 9-16m 2 / g; all ordered from Beijing Juguang Yingnik Technology Co., Ltd.

[0050] MXene is Ti3C2Tx sheet with 1-5 layers and radial size of 0.5-2 μm. It was purchased from Science Compass, item number FMO410206.

[0051] The viscosity average molecular weight of PVP is 3000-7000 and it was purchased from Boai Xinkaiyuan Medical Technology Group Co., Ltd.

[0052] The preparation method of modified PES powder comprises the following steps:

[0053] (1) mixing hydroquinone, 2,5-dihydroxyterephthalic acid, 4,4'-dichlorodiphenyl sulfone, dimethyl sulfoxide, toluene and anhydrous potassium carbonate, wherein the mass ratio of hydroquinone, sodium 3-(4-(-2,6'-difluorophenylcarbonyl)phenyl)propanesulfonate, 4,4'-difluorodiphenyl sulfone, dimethyl sulfoxide, toluene and anhydrous potassium carbonate is 7:14:44:295:120:73; heating to 152°C under nitrogen protection and stirring, keeping the temperature for reaction for 5 hours, raising the temperature to 169°C and continuing the reaction for 5 hours to obtain a polymer product; cooling and solidifying the polymer product, crushing it, washing it with boiling deionized water for 3 times, and then reflux acidifying it with 37wt% hydrochloric acid for 27 hours, filtering it with suction, washing it with deionized water, drying it, and crushing it to a particle size of less than 9μm to obtain a carboxylated modified polyethersulfone powder;

[0054] (2) 3-isocyanate propyl trimethoxysilane (CAS: 15396-00-6, purchased from Shanghai Ruichu Biotechnology Co., Ltd.) and carboxylated modified polyethersulfone powder were mixed and subjected to ultrasonic treatment for 25 minutes; toluene was then added, heated to 107°C and stirred for reaction for 3 hours, and toluene was recovered by vacuum distillation. The solid product was washed twice with ethanol and freeze-dried to obtain silane-modified polyethersulfone powder; the mass ratio of 3-isocyanate propyl trimethoxysilane, carboxylated modified polyethersulfone powder and toluene was 1.1:0.1:65;

[0055] (3) adding 0.03 parts by weight of silane-modified polyethersulfone powder to 32 parts by weight of ethanol and ultrasonicating for 25 minutes to prepare an alcohol solution; weighing 0.03 parts by weight of nano-TiO2 and adding it to 27 parts by weight of deionized water, and ultrasonicating for 25 minutes to prepare a TiO2 aqueous solution;

[0056] (4) Under stirring conditions, the TiO2 aqueous solution is added dropwise to the alcohol solution, and the mass ratio of the silane-modified polyethersulfone powder and nano-TiO2 is 10:3; heated to 60-65°C, stirred for reaction for 3 hours, centrifuged to remove the supernatant, washed with deionized water 3-4 times, and freeze-dried to obtain modified PES powder.

[0057] Nano-TiO2 includes nano-TiO2Ⅰ, nano-TiO2Ⅱ and nano-TiO2Ⅲ with a mass ratio of 1.4:1:0.6; the average primary particle size of TiO2Ⅰ is 15nm, and the specific surface area is 30-100m2 / g (Model DK405); the average primary particle size of nano-TiO2Ⅱ is 60nm, and the specific surface area is 20-60m 2 / g (DK405-2) and the average primary particle size of nano-TiO2Ⅲ is 200nm, and the specific surface area is 15m 2 / g(DK405-3). Purchased from Beijing Dekedao Gold Technology Co., Ltd.

[0058] The surface hydrophilicity of the PES membrane obtained in Example 1 was tested. The sample to be tested was cut into long strips and placed in a vacuum oven for drying. During the test, the volume of the water droplet was controlled to be 3 μl. After it was in contact with the membrane surface for 3 seconds, the image was recorded and the contact angle was analyzed. In order to reduce the error, each group of samples was tested at least three times, and the average value was the contact angle of the sample. See details. Figure 1 .

[0059] The water flux and interception test of the PES composite ultrafiltration membrane modified by MXene material obtained in Example 1 were carried out, and the effective area was selected as 7.07 cm 2 The membrane was tested for permeability and separation performance by cross-flow filtration. Test method: The membrane was initially compacted at a transmembrane pressure of 0.2 MPa for 30 min until a stable water flux was obtained. Then, the working pressure was adjusted to 0.1 MPa and the membrane pure water flux was measured. Pure water flux J (L·m -2 ·h -1 ) is calculated as formula (1):

[0060]

[0061] Where Q(L) is the membrane flow through the effective membrane area A(m) at the operating time T(h) 2 ) of the permeate volume.

[0062] In order to test the separation performance of the membrane, the feed solution was changed to BSA (1 g·L -1 ) and MB (10 mg·L -1 ) solution. Afterwards, the permeate concentration of the obtained membrane was measured by UV spectrophotometer at wavelengths of 280nm and 597nm. The retention rate R (%) of the membrane was estimated using formula (2):

[0063]

[0064] where Cp and Cf represent the concentrations in the permeate and feed solution, respectively.

[0065] The results are as follows Figure 2 shown.

[0066] Example 2

[0067] This embodiment provides a method for preparing a PES composite ultrafiltration membrane modified by a MXene material, comprising the following steps:

[0068] (1) Weigh the corresponding raw materials according to Table 1;

[0069] (2) SnO2, MXene and PVP were dispersed in DMAc and then ultrasonically treated for 1-3 h to obtain a mixture;

[0070] (3) adding the modified PES powder to the mixture and stirring at 90° C. for 4 hours until the PES powder is completely dissolved to obtain a casting solution;

[0071] (4) Defoam the casting liquid and use a casting blade (200 μm) to evenly apply the casting liquid to a smooth glass plate at room temperature. Then slowly place the glass plate in a deionized water condensation bath. As the phase change is completed, the membrane automatically separates from the glass plate. Keep the membrane in deionized water for 12 hours to fully remove excess solvent, thereby obtaining a PES composite ultrafiltration membrane modified based on MXene materials.

[0072] SnO2 includes tin oxide A, tin oxide B and tin oxide C in a mass ratio of 1:1.2:0.4; the average particle size of tin oxide A is 20-50nm, and the specific surface area is 75-98m 2 / g; the average particle size of tin oxide B is 150-200nm, and the specific surface area is 34-51m 2 / g; the average particle size of tin oxide B is 300-400nm, and the specific surface area is 9-16m 2 / g; all ordered from Beijing Juguang Yingnik Technology Co., Ltd.

[0073] MXene is a Ti3C2Tx sheet with 1-5 layers and a radial size of 0.5-2μm.

[0074] The viscosity average molecular weight of PVP is 3000-7000 and it was purchased from Boai Xinkaiyuan Medical Technology Group Co., Ltd.

[0075] The preparation method of modified PES powder comprises the following steps:

[0076] (1) mixing hydroquinone, 2,5-dihydroxyterephthalic acid, 4,4'-dichlorodiphenyl sulfone, dimethyl sulfoxide, toluene and anhydrous potassium carbonate, wherein the mass ratio of hydroquinone, sodium 3-(4-(-2,6'-difluorophenylcarbonyl)phenyl)propanesulfonate, 4,4'-difluorodiphenyl sulfone, dimethyl sulfoxide, toluene and anhydrous potassium carbonate is 6:13:43:290:120:72; heating to 150°C under nitrogen protection and stirring, keeping the temperature for reaction for 4 hours, raising the temperature to 168°C and continuing the reaction for 4 hours to obtain a polymer product; cooling and solidifying the polymer product, crushing it, washing it twice with boiling deionized water, and then reflux acidifying it with 36wt% hydrochloric acid for 25 hours, filtering it with suction, washing it with deionized water, drying it, and crushing it to a particle size of less than 9μm to obtain a carboxylated modified polyethersulfone powder;

[0077] (2) 3-isocyanate propyl trimethoxysilane (CAS: 15396-00-6, purchased from Shanghai Ruichu Biotechnology Co., Ltd.) and carboxylated modified polyethersulfone powder were mixed and ultrasonicated for 30 minutes; toluene was then added, heated to 105°C and stirred for reaction for 2-3 hours, and toluene was recovered by vacuum distillation. The solid product was washed twice with ethanol and freeze-dried to obtain silane-modified polyethersulfone powder; the mass ratio of 3-isocyanate propyl trimethoxysilane, carboxylated modified polyethersulfone powder and toluene was 1:0.1:60;

[0078] (3) adding 0.03 parts by weight of silane-modified polyethersulfone powder to 30 parts by weight of ethanol and ultrasonicating for 20 minutes to prepare an alcohol solution; weighing 0.03 parts by weight of nano-TiO2 and adding it to 25 parts by weight of deionized water, and ultrasonicating for 20 minutes to prepare a TiO2 aqueous solution;

[0079] (4) Under stirring conditions, the TiO2 aqueous solution was added dropwise to the alcohol solution, and the mass ratio of silane-modified polyethersulfone powder to nano-TiO2 was 10:1; heated to 60°C, stirred for reaction for 2 hours, centrifuged to remove the supernatant, washed three times with deionized water, and freeze-dried to obtain modified PES powder.

[0080] Nano-TiO2 includes nano-TiO2Ⅰ, nano-TiO2Ⅱ and nano-TiO2Ⅲ with a mass ratio of 1.3:1:0.5; the average primary particle size of TiO2Ⅰ is 15nm, and the specific surface area is 30-100m 2 / g (Model DK405); the average primary particle size of nano-TiO2Ⅱ is 60nm, and the specific surface area is 20-60m 2 / g (DK405-2) and the average primary particle size of nano-TiO2Ⅲ is 200nm, and the specific surface area is 15m 2 / g(DK405-3). Purchased from Beijing Dekedao Gold Technology Co., Ltd.

[0081] The self-cleaning performance of the PES composite ultrafiltration membrane modified based on MXene materials obtained in Example 2 was tested. The self-cleaning performance of membrane M4 was evaluated by ultraviolet irradiation (365nm, 36W) experiment. Test method: The unstable MB (10mg·L-1) dye deposits on the membrane surface were first washed with deionized water. The contaminated membrane was then immersed in deionized water and placed under ultraviolet light for photodegradation until the membrane surface was close to the original color and then removed. The separation performance of the treated membrane was then tested again. Repeat the above steps for a total of three cycles of testing.

[0082] Test results such as Figure 3 As shown in the figure, with the increase of filtration time, the deposition of dye molecules on the membrane surface leads to the clogging of surface pores, which increases the retention of MB molecules, resulting in a gradual decrease in the permeation flux of water molecules through the membrane. Subsequently, under the irradiation of ultraviolet light, SnO2 generates photogenerated electrons, which promotes the decomposition of the dye and thus promotes the recovery of membrane flux. After three cycles of testing, the MB retention rate is still higher than 95%, which proves that long-term illumination conditions and the effect of oxides will not damage the membrane structure.

[0083] Example 3

[0084] The difference between this embodiment and embodiment 1 is that the mass percentage of the raw materials in Table 1 is different.

[0085] The flux and retention test of methylene blue were carried out on the PES composite ultrafiltration membrane modified by MXene material obtained in Example 3. The results are as follows: Figure 4 shown.

[0086] Comparative Example 1

[0087] The difference between this comparative example and Example 1 is that the mass percentage of the raw materials in Table 1 is different.

[0088] Comparative Example 2

[0089] The difference between this comparative example and Example 1 is that the mass percentage of the raw materials in Table 1 is different.

[0090] Comparative Example 3

[0091] The difference between this comparative example and Example 1 is that the mass percentage of the raw materials in Table 1 is different.

[0092] Comparative Example 4

[0093] The difference between this comparative example and Example 1 is that the preparation method of the modified PES powder is different.

[0094] The preparation method of modified PES powder comprises the following steps: mixing hydroquinone, 2,5-dihydroxyterephthalic acid and 4,4'-dichlorodiphenyl sulfone, dimethyl sulfoxide, toluene and anhydrous potassium carbonate, wherein the mass of hydroquinone, sodium 3-(4-(-2,6'-difluorophenylcarbonyl)phenyl)propanesulfonate, 4,4'-difluorodiphenyl sulfone, dimethyl sulfoxide, toluene and anhydrous potassium carbonate is 7:14:44:295:120:73; heating to 152°C under nitrogen protection and stirring, keeping the temperature for reaction for 5 hours, heating to 169°C and continuing the reaction for 5 hours to obtain a polymer product; cooling and solidifying the polymer product, crushing it, washing it with boiling deionized water for 3 times, and then refluxing and acidifying it with hydrochloric acid with a concentration of 37wt% for 27 hours, filtering it, washing it with deionized water, drying it, and crushing it to a particle size of less than 9μm to obtain a modified polyethersulfone powder.

[0095] Comparative Example 5

[0096] The difference between this comparative example and Example 1 is that SnO2 comprises tin oxide A, tin oxide B and tin oxide C in a mass ratio of 1:1:1; the average particle size of tin oxide A is 20-50nm, and the specific surface area is 75-98m 2 / g; the average particle size of tin oxide B is 150-200nm, and the specific surface area is 34-51m 2 / g; the average particle size of tin oxide B is 300-400nm, and the specific surface area is 9-16m 2 / g; all ordered from Beijing Juguang Yingnik Technology Co., Ltd.

[0097] Comparative Example 6

[0098] The difference between this comparative example and Example 1 is that the modified PES powder is replaced by commercially available PES powder, and the commercially available PES powder is purchased from Science Compass, item number FMO410206.

[0099] Comparative Example 7

[0100] The difference between this comparative example and Example 1 is that the nano-TiO2 comprises nano-TiO2Ⅰ, nano-TiO2Ⅱ and nano-TiO2Ⅲ in a mass ratio of 1:1:1; the average primary particle size of TiO2Ⅰ is 15nm, and the specific surface area is 30-100m 2 / g (Model DK405); the average primary particle size of nano-TiO2Ⅱ is 60nm, and the specific surface area is 20-60m 2 / g (DK405-2) and the average primary particle size of nano-TiO2Ⅲ is 200nm, and the specific surface area is 15m 2 / g(DK405-3). Purchased from Beijing Dekedao Gold Technology Co., Ltd.

[0101] Performance Testing

[0102] The MXene-modified PES composite ultrafiltration membranes prepared in Examples 1-3 and Comparative Examples 1-7 were cut into circular membrane sheets with a diameter of 5 cm, loaded into a membrane pool, and pre-pressed at 0.15 MPa for 30 min. Then, at 25°C and 0.1 MPa, the 3 wt% BSA (bovine serum albumin) solution flux of each group of MXene-modified PES composite ultrafiltration membranes was measured by cross-flow filtration. The volume of the 3 wt% BSA solution passing through the membrane within a certain period of time was recorded, and the 3 wt% BSA solution flux of the membrane was calculated by the formula.

[0103]

[0104] Where: JW is the flux of 3 wt% BSA solution of the membrane (L·m -2 ·h -1 ); Vt is the volume of 3 wt % BSA solution that permeates within △t time (L); A is the effective area of ​​the membrane (m 2 ) ; △t is the sample connection time (h). After the flux is stable, take the permeate and raw liquid water samples respectively, measure their absorbance by ultraviolet spectrophotometer, the measuring wavelength is 280nm, and then calculate the retention rate of the membrane by Lambert Beer's law.

[0105]

[0106] Wherein: R is the retention rate (%) of the PES composite ultrafiltration membrane modified based on MXene material for BSA solution; At is the absorbance value of the raw material solution; A0 is the absorbance value of the permeate.

[0107] The above-mentioned groups of PES composite ultrafiltration membranes modified by MXene materials were run in a 3% BSA solution with the same parameters for 96 hours, and their fluxes were measured. Then, the fluxes were measured again after washing, and the flux changes were observed and the data were recorded.

[0108] The results are shown in Table 1.

[0109] Table 1 Performance test results of PES composite ultrafiltration membrane modified by MXene materials

[0110] Flux Retention rate Flux after 96h Flux after washing unit <![CDATA[L·m -2 ·h -1 ]]> % <![CDATA[L·m -2 ·h -1 ]]> <![CDATA[L·m -2 ·h -1 ]]> Example 1 202.5 98.34 152.6 193.7 Example 2 200.8 97.87 147.1 190.2 Example 3 201.2 97.92 151.2 191.4 Comparative Example 1 170.8 96.24 104.55 147.6 Comparative Example 2 182.2 96.87 112.91 159.7 Comparative Example 3 184.7 96.91 115.46 157.9 Comparative Example 4 173.5 96.12 108.23 144.2 Comparative Example 5 181.3 94.79 118.08 158.4 Comparative Example 6 160.9 95.88 89.67 134.8 Comparative Example 7 192.6 97.24 145.37 175.4

[0111] From the above performance test results, it can be seen that Example 1-2 has high flux and retention rate and good stability.

[0112] However, the comparative example is significantly worse than the embodiment in the corresponding performance test because the necessary technical scheme is not adopted. In comparative example 1, MXene and tin oxide are not added. It can be seen that the comprehensive performance effect of the PES composite ultrafiltration membrane modified by MXene material is reduced. MXene is not used in comparative example 2, and tin oxide is not added in comparative example 3. From the results, it can be seen that the performance of the PES composite ultrafiltration membrane modified by MXene material is affected, indicating the synergistic effect of the compounding of the two. Nano-titanium oxide is not grafted in comparative example 4, and the ratio of nano-titanium oxide in comparative example 7 is different. The flux and retention rate of the PES composite ultrafiltration membrane modified by MXene material are reduced. The particle size ratio of tin oxide in comparative example 5 is different, and the flux and retention rate of the PES composite ultrafiltration membrane modified by MXene material are reduced. In comparative example 6, the modified PES powder is replaced with commercially available PES powder, and the performance of the PES composite ultrafiltration membrane modified by MXene material is lower than that of Examples 1-3. The above experimental results further prove the importance of the technical scheme defined in the present invention for its technical effect.

[0113] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a PES composite ultrafiltration membrane modified by MXene material, characterized in that: The following steps are involved: (1) Weigh the raw materials according to the following mass percentages: 16-20% modified PES powder, 0.08-0.13% SnO2, 0.01-0.03% MXene, 0.8-1.5% PVP and the balance DMAc; (2) SnO2, MXene and PVP were dispersed in DMAc and then ultrasonically treated for 1-3 h to obtain a mixture; (3) adding the modified PES powder to the mixture and stirring at 60-90° C. for 4-8 hours until the PES powder is completely dissolved to obtain a casting solution; (4) Defoam the casting liquid and evenly apply the casting liquid to a glass plate at room temperature. Then place the glass plate in a deionized water condensation bath. As the phase change is completed, the membrane automatically separates from the glass plate. Keep the membrane in deionized water for 12-24 hours to obtain a PES composite ultrafiltration membrane modified based on MXene materials.

2. The method for preparing a PES composite ultrafiltration membrane modified by MXene material according to claim 1, characterized in that: SnO2 includes tin oxide A, tin oxide B and tin oxide C in a mass ratio of 1: (1.2-1.5): (0.4-0.7); the average particle size of tin oxide A is 20-50nm, and the specific surface area is 75-98m 2 / g; the average particle size of tin oxide B is 150-200nm, and the specific surface area is 34-51m 2 / g; the average particle size of tin oxide B is 300-400nm, and the specific surface area is 9-16m 2 / g.

3. The method for preparing a PES composite ultrafiltration membrane modified by MXene material according to claim 1, characterized in that: MXene is a Ti3C2Tx sheet with 1-5 layers and a radial size of 0.5-2μm.

4. The method for preparing a PES composite ultrafiltration membrane modified by MXene material according to claim 1, characterized in that: The viscosity average molecular weight of PVP is 3000-7000.

5. The method for preparing a PES composite ultrafiltration membrane modified by MXene material according to claim 1, characterized in that: The preparation method of modified PES powder comprises the following steps: (1) mixing hydroquinone, 2,5-dihydroxyterephthalic acid, 4,4'-dichlorodiphenyl sulfone, dimethyl sulfoxide, toluene and anhydrous potassium carbonate, heating to 150-155° C. under nitrogen protection and stirring, keeping the temperature for reaction for 4-6 hours, raising the temperature to 168-170° C. and continuing the reaction for 4-6 hours to obtain a polymerization product; cooling and solidifying the polymerization product, crushing, washing, reflux acidification, suction filtering, washing, drying, and crushing to a particle size of less than 9 μm to obtain a carboxylated modified polyether sulfone powder; (2) 3-isocyanate propyltrimethoxysilane and carboxylated modified polyethersulfone powder are mixed and subjected to ultrasonic treatment for 20-30 minutes; toluene is then added, heated to 105-100° C. and stirred for reaction for 2-3 hours, toluene is recovered by vacuum distillation, the solid product is washed, and freeze-dried to obtain silane-modified polyethersulfone powder; (3) adding 0.03 parts by weight of silane-modified polyethersulfone powder to 30-35 parts by weight of ethanol and ultrasonicating for 20-30 minutes to prepare an alcohol solution; weighing 0.03 parts by weight of nano-TiO2 and adding it to 25-30 parts by weight of deionized water, and ultrasonicating for 20-30 minutes to prepare a TiO2 aqueous solution; (4) Under stirring conditions, the TiO2 aqueous solution is added dropwise to the alcohol solution, heated to 60-65°C, stirred for reaction for 2-4 hours, centrifuged to remove the supernatant, washed, and freeze-dried to obtain modified PES powder.

6. The method for preparing a PES composite ultrafiltration membrane modified by MXene material according to claim 5, characterized in that: The masses of hydroquinone, sodium 3-(4-(-2,6'-difluorophenylcarbonyl)phenyl)propanesulfonate, 4,4'-difluorodiphenyl sulfone, dimethyl sulfoxide, toluene and anhydrous potassium carbonate are (6-8):(13-15):(43-45):(290-300):120:(72-75).

7. The method for preparing a PES composite ultrafiltration membrane modified by MXene material according to claim 5, characterized in that: The mass ratio of 3-isocyanatepropyltrimethoxysilane, carboxylation-modified polyethersulfone powder and toluene is (1-1.2):0.1:(60-70).

8. The method for preparing a PES composite ultrafiltration membrane modified by MXene material according to claim 5, characterized in that: The mass ratio of silane-modified polyethersulfone powder to nano-TiO2 is 10:(1-3).

9. The method for preparing a PES composite ultrafiltration membrane modified by MXene material according to claim 1, characterized in that: Nano-TiO2 includes nano-TiO2Ⅰ, nano-TiO2Ⅱ and nano-TiO2Ⅲ with a mass ratio of (1.3-1.5):1:(0.5-0.7); The average primary particle size of TiO2Ⅰ is 15nm, and the specific surface area is 30-100m 2 / g; the average primary particle size of nano-TiO2Ⅱ is 60nm, and the specific surface area is 20-60m 2 / g and the average primary particle size of nano-TiO2Ⅲ is 200nm, and the specific surface area is 15m 2 / g.

10. A PES composite ultrafiltration membrane modified by MXene material obtained by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of polyvinylidene fluoride mixed matrix membrane

    CN111760461A

  • Composite separation membrane with photocatalytic self-cleaning function as well as preparation method and application of composite separation membrane

    CN115282787A

  • Method for manufacturing membrane using selective layer prepared through support-free interfacial polymerization

    US20180141831A1

  • Dialysis system incorporating a toxin-removal loop

    US20240238493A1